A weather-driven mathematical model of Culex population abundance and the impact of vector control interventions - Suman Bhowmick; Patrick Irwin; Kristina Lopez; Megan Lindsay Fritz; Rebecca Lee Smith (Ecological Informatics)
Even as the incidence of mosquito-borne diseases like West Nile Virus (WNV) in North America has risen over the past several decades, effectively modelling mosquito population density or abundance has proven to be a persistent challenge. It is critical to capture the fluctuations in mosquito abundance across seasons in order to forecast the varying risk of pathogen transmission from one year to the next. We develop a process-based mechanistic weather-driven Ordinary Differential Equation (ODE) model to study the population biology of both aquatic and terrestrial stages of mosquito population. The progression of mosquito lifecycle through these stages is influenced by different factors, including temperature, daylight hours, intra-species competition and the availability of aquatic habitats. In our work, weather-driven parameters are derived from a combination of laboratory research and data from the literature. In our model, we include precipitation data as a substitute for evaluating additional mortality in the mosquito population. We compute the Basic offspring number of the associated model and perform sensitivity analysis. Finally, we employ our model to assess the effectiveness of various adulticides strategies to predict the reduction in mosquito population. This enhancement in modelling of mosquito abundance can be instrumental in guiding interventions aimed at reducing mosquito populations and mitigating mosquito-borne diseases such as the WNV. This model could help optimise the timing of adulticide applications and evaluate the impact of multiple spray events within a short period.